Parallel evolution of chordate cis-regulatory code for development. - Laura Doglio; Debbie K Goode; Maria C Pelleri; Stefan Pauls; Flavia Frabetti; Sebastian M Shimeld; Tanya Vavouri; Greg Elgar (PLoS Genetics)
Urochordates are the closest relatives of vertebrates and at the larval stage, possess a characteristic bilateral chordate body plan. In vertebrates, the genes that orchestrate embryonic patterning are in part regulated by highly conserved non-coding elements (CNEs), yet these elements have not been identified in urochordate genomes. Consequently the evolution of the cis-regulatory code for urochordate development remains largely uncharacterised. Here, we use genome-wide comparisons between C. intestinalis and C. savignyi to identify putative urochordate cis-regulatory sequences. Ciona conserved non-coding elements (ciCNEs) are associated with largely the same key regulatory genes as vertebrate CNEs. Furthermore, some of the tested ciCNEs are able to activate reporter gene expression in both zebrafish and Ciona embryos, in a pattern that at least partially overlaps that of the gene they associate with, despite the absence of sequence identity. We also show that the ability of a ciCNE to up-regulate gene expression in vertebrate embryos can in some cases be localised to short sub-sequences, suggesting that functional cross-talk may be defined by small regions of ancestral regulatory logic, although functional sub-sequences may also be dispersed across the whole element. We conclude that the structure and organisation of cis-regulatory modules is very different between vertebrates and urochordates, reflecting their separate evolutionary histories. However, functional cross-talk still exists because the same repertoire of transcription factors has likely guided their parallel evolution, exploiting similar sets of binding sites but in different combinations.